2022
DOI: 10.1002/rse2.260
|View full text |Cite
|
Sign up to set email alerts
|

Land cover classification of treeline ecotones along a 1100 km latitudinal transect using spectral‐ and three‐dimensional information from UAV‐based aerial imagery

Abstract: The alpine treeline ecotone is expected to move upwards in elevation with global warming. Thus, mapping treeline ecotones is crucial in monitoring potential changes. Previous remote sensing studies have focused on the usage of satellites and aircrafts for mapping the treeline ecotone. However, treeline ecotones can be highly heterogenous, and thus the use of imagery with higher spatial resolution should be investigated. We evaluate the potential of using unmanned aerial vehicles (UAVs) for the collection of ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 86 publications
2
18
0
Order By: Relevance
“…are common in the ground layer. Detailed information about the vegetation at our study sites is given by Mienna et al 34 .
Figure 1 Map showing the 14 study sites located along a 500 km latitudinal gradient in northern Norway.
…”
Section: Methodsmentioning
confidence: 99%
“…are common in the ground layer. Detailed information about the vegetation at our study sites is given by Mienna et al 34 .
Figure 1 Map showing the 14 study sites located along a 500 km latitudinal gradient in northern Norway.
…”
Section: Methodsmentioning
confidence: 99%
“…Mountain birch is the dominating treeline-forming species, but other tree species such as Norway spruce (Picea abies), Scots pine (Pinus sylvestris), rowan (Sorbus aucuparia), and aspen (Populus tremula) are present. The vegetation varies within and between sites, with vegetation types such as ridges, lee sides, and snowbeds typically being found across the whole transect (Mienna et al, 2022b). The mountainous areas in Norway have a long land use history, and it is likely that the current treeline positions at the sites are legacies of earlier land use (Bryn & Potthoff, 2018).…”
Section: Study Sitesmentioning
confidence: 99%
“…The mountainous areas in Norway have a long land use history, and it is likely that the current treeline positions at the sites are legacies of earlier land use (Bryn & Potthoff, 2018). More background information about the transect and study sites can be found in Thieme et al (2011), Mienna et al (2020), andMienna et al (2022b).…”
Section: Study Sitesmentioning
confidence: 99%
See 2 more Smart Citations